PERILAKU ORGANISASIONAL PADA IMPLEMENTASI SISTEM INFORMASI KEUANGAN DAERAH (SIKD) (Studi Empiris Pada Pemerintah Daerah Kabupaten Sragen) - Supartini, Supartini (Fakultas Ekonomi dan Bisnis Universitas Ahmad Dahlan, 2011)
Local Financial Information System (SIKD) can give the better information for the decision making of strategic specially relate to the transparency and accountability in public sector. This research aim to test the relation between SKID implementation factor that supported, clarity of target, training with the cognitive conflict, affective conflict,the usefulness of SIKD, then cognitive and affective conflict by usefulness of SIKD and also the relation of SIKDâs usefulness by cost consciousness. Data obtained by propagating questioner to head on duty, chief, the institutionâs leader, the areaâs leader, superintendent, secretary of area and secretary DPRD of local government of Sragen Regency. The result of this research supports Chenhall (2004) which indicates the usefulness of ABCM for the scheme of product related to the financial succeed. This research suggests that in the system implementation, pays attention to other factors and requires to be developed to check the technical factors.